P138 Basal plasma cells in normal large bowel: what is normal?. (15th January 2020) - Castelli, P; Abuquteish, D; Di Ruscio, M; Lunardi, G; Zamboni, G; Riddell, R
Abstract: Background: Basal plasma cells (BPC) are a diagnostic criterion for inflammatory bowel disease (IBD) and their persistence following therapy also indicates an increased risk of relapse. However neither the definition of basal plasma cells nor what is normal has been well established. We examined these parameters and determined whether there is reginal variability throughout the large bowel. Methods: We looked at two patient populations. Group A) Biopsies from 6 standardised sites around the colon (cecum to rectum) from 37 patients who had normal colonoscopy at IRCCS Sacro Cuore Hospital, Negrar, Verona, Italy for symptoms suggesting irritable bowel syndrome, who were free of all medical therapy. Group B) a validation cohort from Mt Sinai Hospital Toronto using sections from the same 6 sites from 16 subtotal and total colectomy specimens performed for non-obstructing colonic carcinoma, primarily Lynch syndrome. Basal plasma cells were counted between two crypts in both the basal 5%, and the basal 20% of the mucosa. A partitioned visual analogue scale (PVAS) was also developed to see if this could replace counting, especially as the distance between crypts in IBD is variable Results: In group A, in the lowest 5% part of the lamina propria, basal plasma cells were found throughout the large bowel and were highest in the proximal colon and lowest in the rectosigmoid. The maximum number of plasma cells between crypts was seven for the cecum and two for the rectum, with a gentle gradation between these two. The PVAS (range 1–5) varied from a maximum of 2 proximally to 1 distally. When the basal 20% was counted, the scores ranged from 35 in the cecum to 12 in the rectum, again with a gradation between, but the PVAS increased from a maximum of 3 proximally to 2 in the rectum. In group B the results were virtually to Group A and the PVAS scores were also virtually identical, The main difference was that at least one plasma cell was seen in all sections, likely because tissue sections encompass a much larger area. These results were all statistically significant. Conclusion: The normal large bowel has a gradation of plasma cells that is highest proximally and lowest distally, however assessed, and needs to be taken into account when assessing the presence of basal plasma cells as an indicator of increased likelihood of relapse of IBD. The PVAS developed can replace the chore of counting, and is likely more meaningful when architectural distortion is present.